Mission San Buenaventura - Hubert A. Lowman::::::photographer::: (H. S. Crocker Company, Inc.)
Altar and general interior of Mission San Buenaventura. Back of postcard reads: 'Founded 1782, Ventura, California. Beautiful interior of the ninth and last mission founded by Father Junipero Serra in California.' An official California Mission Trails Association card.